Connecting Phonology with Semantics: A Case Study of Polyphones and Homographs in the Written Essays of Some Obafemi Awolowo University English Students - Yemisi M. Famakinwa; Oluwaseun M. Olagunju (CV. Rustam, 2025)
The study considers the relationship between semantics and phonology. Hence, the need for the identification and categorization of samples of homographs (in semantics) and polyphones (in phonology), respectively. Data for the research are gathered from the written essays (academic writing) of some English students of Obafemi Awolowo University; Ile-Ife, Nigeria. The students’ essays are subject to purposive sampling in order to bring out representative samples of homographs and polyphones. Driven by insight from related research on homography and polyphony as well as Halliday's Systemic Functional Theory, findings reaffirm that both semantics and phonology are interrelated because the written discourse of the English language is systemic and, thus, thrives on meaning-related approaches. Findings further reveal that there is indeed a discrepancy between homography and polyphony. The discrepancy, as discovered from the gathered samples, appears rather cumbersome and challenging, especially for learners of English as a Second Language (ESL). The study concludes by recommending that in the teaching of homography and polyphony, students as well as learners of English as a Second Language (ESL) must be painstakingly put through the similarities, differences and distinct samples of homographs and polyphones. This, in linguistic inquiry, is needful for meaningful interpretation of homography and polyphony, respectively.